INVESTIGATION OF HYDRO-IMPULSE PARAMETERS ON HORIZONTAL SURFACE DURING PULSATIONS OF HYDROGEN BURNING PRODUCTS - D. A. Kozlov; V. V. Ivashechkin; D. A. Prokopchuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The paper provides a methodology and measurement results of pressure impulses and tangential stresses initiated on a flat wall while burning a gas mixture 2H2 + O2 in a chamber installed above horizontal surface. Pressure and tangential stress distribution along the surface length at various distances to the chamber with its various gas mixture filling is revealed in the paper.